Edukasi Tentang Corona Virus Disease-2019 (Covid-19) Di Desa Bangga Kabupaten Sigi Sulawesi Tengah - Rosita Rosita; Nur Febrianti; Yulta Kadang (Idea Pengabdian Masyarakat, 2022)
Corona Virus Disease-2019 (Covid-19) is an infectious disease caused by a new type of corona virus, namely SARS-CoV-2. Since December 2019, the number of confirmed cases of COVID-19 has continued to increase. Covid-19 has become a pandemic that has attacked many countries globally and has infected more than 243,561,596 cases with 4,947,777 human deaths in 204 infected countries and 151 community transmission countries. In Indonesia, on October 26, 2021, there were 4,241,090 confirmed cases with 143,270 deaths from the total confirmed cases. Central Sulawesi Province with 1.1% of the total confirmed cases in Indonesia or 46,959 cases and Sigi Regency being the fifth highest number of confirmed cases with 3,556 cases. Seeing the high incidence of Covid-19 cases in Sigi Regency, it is very necessary to provide health education about Covid-19in the form of community service activities by providing education and a good understanding of Covid-19. The method of implementing community service is carried out by health counseling techniques with counseling media using Flip Charts and Leaflets. The results of this community service show that many participants ask questions directly and the evaluation results from the questionnaires given show that the community has a good understanding by answering each question correctly and is very enthusiastic. Health education activities for the community in Bangga Village, Sigi Regency are very important to increase public knowledge about Covid-19, its signs and symptoms, causes and prevention efforts so that the community can minimize the risk of transmission in the surrounding environment.